Conversations about inclusion in an AIAEE Context: A Review of Radical Inclusion: What the Post-9/11 world should have taught us about leadership - Glen C. Shinn; R. Kirby Barrick (Journal of International Agricultural and Extension Education, 2018)
Martin Dempsey, U.S. Army Ret. and Rubenstein Fellow at Duke University, and Ori Brafman, a Distinguished Teaching Fellow at UC Berkeley with research in distributed networks, have analyzed today’s leadership landscape. Popular press reviews of the 2017 book, Radical Inclusion, report broad implications for corporate leadership and organizational improvement. This review compares and contrasts Dempsey and Brafman’s leadership principles with implications and applications for international agricultural and extension education networks.
Keywords: Agriculture; Collaboration; Education; Extension; Impact; Inclusion